The problematic of civil society in contemporary Arab thought –Azmi Bishara is a model - charghi, younes (Journal of Social Sciences and Humanities, 2021)
This study aims to reveal the circumstances of the emergence of the idea of the civil society in the Arab experience, through the critical project presented by Azmi Bishara, and that by focusing on the idea as a political and philosophical figure , through rooting its concepts and dismantling them from their beginnings to the actual representations of them in the contemporary Arab thought and searching for the civil society as a multi conceptual philosophical idea that lead us towards the path of uncovering borders that closely matches the conforming of the Arab case. And on the historical tasks of Arab civil society and its role in the existing developments in reality that includes the revealing of cognitive drivers that drive towards shaping the features of this civil society. In this study, we relied on updating the analytical information in the reading of Azmi Bishara by exploring his philosophical presentation on the subject in his studies presented in the Arab intellectual arena And we supported the study with a personal interview documented with him to review the theory under the light of the Arab situation that was produced by the events of the Arab Spring since the end of 2010, in which each track was tracked and its impact on the development of the concept, based on the dialectic of the direct relationship with the concept of democracy, and this last , lead to this question about the political duty of the pioneers of the civil society idea and their basic obligations before the concept is removed from the theoretical circle towards the application one, and the major dilemma remains in this concept, Represented by the ready import of it from the Western intellectual experience which caused the burning of philosophical and historical stages that resulted some contradictions which distorted the essence of the civil society and derived it from its historical context that corresponds to its accumulative stations. Eventually, we have tried to go back to the origin of this issue and to seek to get out of it with an answer committed to stimulating the debate again in order to alleviate the disadvantages of burning the stages as mentioned before..